Challenging Gender Inequality Through Deconstructing Power Dynamics: Nawal El Saadawi and Egyptian Family Law - Dede Permana; Cecep Soleh Kurniawan; Ahmad Jamaludin Jambunanda (MUWAZAH : jurnal kajian gender, 2024)
This article aims to examine the power dynamics in Egyptian family law and the challenges encountered in achieving gender equality. The focus is on Nawal El Saadawi's role in pushing for more inclusive family law change. The research findings reveal discriminatory practices against women in Egyptian family law, particularly in marriage, divorce, child custody, and inheritance. Nawal El Saadawi's strategies and activism aim to address and confront gender inequality within family law. The study has contributed to a shift towards a more inclusive understanding of family law. Nawal El Saadawi has had a positive impact in improving the protection of women's rights. This research confirms the important role of women like Nawal El Saadawi as agents of social change. The research uses qualitative methods with library research. Primary data sources are the works of Nawal Saadawi that discusses the theme of Egyptian family law, secondary sources of data are other literature relevant to the topic discussed are also used in the research. Research findings focused on discrimination against women in Egyptian family law.  She highlighted several aspects such as divorce procedures, polygamy, bait at tho’ah, livelihoods, and gifts that were judged to be detrimental to women. The research will develop concrete recommendations that can be used as a guide to address the gender gap that still exists in family law and to analyze the influence of social change on existing power dynamics and the position of women in a family environment.